Analysis of hematological parameters in bladder cancer in early and advanced stages at Dr. Sardjito Hospital - Hidayu Permata Hardi; Indrawarman Soerohardjo; Ahmad Zulfan Hendri (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Bladder cancer (BC) is the tenth most common cancer in both males and females. Early detection can improve the patient's chances of survival, giving patients with BC a good prognosis. The hematological parameter determines the number of leukocytes, hemoglobin, platelets, and Neutrophil-Lymphocyte Ratio (NLR) in the body. The presence of abnormal values on hematological parameters indicates that the patient is in poor condition.Objective: This study aims to compare hematological parameters between early-stage and advanced BC at Dr. Sardjito Hospital.Methods: This study was a retrospective cross-sectional study using patient medical records. By using the results of the anatomical pathology, pre-operative hematology evaluated the influence on the bladder cancer stage. The sample used consisted of 130 bladder cancer patients. Chi-square and regression statistical tests were used to analyze the collected data.Results: The advanced-stage group had considerably higher leukocytosis than the early-stage group (p = 0.000). Anemia predominated more in the later-stage group than in the earlier stage (p = 0.048). Additionally, the advanced-stage group experienced thrombocytosis more frequently than the early-stage group (p = 0.000). NLR was higher in the advanced compared to the early-stage group (p = 0.000).Conclusion: Patients with advanced bladder cancer were more likely to experience abnormal hematological parameters levels than those with the earliest stages of the disease.